DIGITALIZATION OF THE NATIONAL ECONOMY HOW TO RESPOND TO UKRAINE’S INTEGRATION CHALLENGES - Вапирова, Евгения (SWorldJournal, 2021)
The article considers the trends of digitalization of the economy of Ukraine, highlights the main directions of innovation and digital development, analyzes the dynamics of demandIT-sector, the influence of innovative technologies on qualitative transfor